Legal Protection for Micro, Small, and Medium Enterprises in the Perspective of Job Creation Act - Susetyo Rohadi; Iryani, Dewi; Setiawan, Puguh Aji Hari (Universitas Serang Raya, 2024)
The Job Creation Law, or often referred to as the Omnibus Law, has become a hot topic of debate in the community. On one hand, there are those who support this law on the grounds that it can accelerate economic growth and create new jobs. History shows that MSMEs have tremendous resilience in the face of economic crises. When the economic crisis hit in 1998 and 2008, MSMEs were relatively able to survive compared to large companies. Despite their great potential, MSMEs in Indonesia face various challenges. One of the main challenges is limited access to financing. Many MSMEs struggle to obtain sufficient working capital to expand their businesses. In addition, the low level of education and skills of the workforce is also an obstacle in improving the productivity and competitiveness of MSMEs. The research process using literature studies began with a descriptive qualitative research type. Legal protection for MSMEs is currently better regulated through the Job Creation Law and Government Regulation Number 7 of 2021. Both regulations pay special attention to financing and legal assistance for MSMEs, including legal counseling, legal consultation, mediation, and out-of-court assistance